The book of life eaudiobook A novel. - Harkness, Deborah (All Souls, 2021)
The #1 New York Times bestselling third installment in the All Souls series, from the author of The Discovery of Witches and The Black Bird Oracle. Look for the hit series “A Discovery of Witches,” now streaming on AMC+, Sundance Now, and Shudder! Bringing the magic and suspense of the All Souls Trilogy to a deeply satisfying conclusion, this highly anticipated finale went straight to #1 on the New York Times bestseller list. In The Book of Life, Diana and Matthew time-travel back from Elizabethan London to make a dramatic return to the present—facing new crises and old enemies. At Matthew’s ancestral home, Sept-Tours, they reunite with the beloved cast of characters from A Discovery of Witches —with one significant exception. But the real threat to their future has yet to be revealed, and when it is, the search for Ashmole 782 and its missing pages takes on even more urgency.